Comparative Performance on Derivatives Usage between Islamic and Conventional Banks in Malaysia - Alwi, Shaliza; Kamaruddin, Halim Shukri; Najaf , Khakan; Salleh, Masrina Nadia Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The action of derivative trading has accelerated in the world especially towards the financial and economic markets around the globe. Since the instruments of derivatives are increasingly used in most of the banks, investment activities have been altered due to the factors that led the scenario of Lehman Holding Inc. as well as the conditions that brought about the 2007 subprime crisis. The aim of this study is to assess the evaluation of the performance of four commercial banks and two other Islamic banks. The collected sample secondary data in this case about Derivatives is categorized into two sections that is from 2010 to 2018 and the other phase is from 2015 to 2018. The four commercial banks include Public Bank, Maybank, RHB and Hong Leong Bank whereas Islamic banks include Maybank Islamic and AmBank Islamic. Therefore, the secondary data on commercial and Islamic banks about the Total Derivative Assets (TDA), Total Liabilities (TL), Earnings Per Share (EPS), Total Net Income (TNI), Inflation Consumer Annual Prices (I), Total Deposits (TD) and GDP Annual Growth in percentage all from the financial statements from the specified banks.